2021
DOI: 10.1055/a-1490-8493
|View full text |Cite
|
Sign up to set email alerts
|

Short versus standard esophageal myotomy in achalasia patients: a systematic review and meta-analysis of comparative studies

Abstract: Background and study aims Despite the clinical efficacy of peroral endoscopic myotomy (POEM), postoperative symptomatic gastroesophageal reflux disease (GERD) remains a major concern. While it is known that length of the gastric myotomy affects postoperative GERD, the clinical relevance of variation in esophageal myotomy length is not well known. We performed a systematic review and meta-analysis of studies comparing outcomes of short versus standard myotomy length in patients with achalasia. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…[23,24] In addition, a comparison of the efficacy of various operation methods of POEM has gradually emerged, such as anterior versus posterior direction anterior versus posterior myotomy [25] and short versus standard esophageal myotomy. [26] At the same time, studies on the efficacy of POEM in the treatment of special populations such as the pediatric, [27] the geriatric, [28] the failed Heller myotomy patients, [29] and other esophageal motility disorders patients [30] are also gradually emerging. Recently, the efficacy of the derivative technology of POEM, such as D-POEM for esophageal diverticulum, [31] Z-POEM for Zenker diverticulum, [19] and G-POEM for refractory gastroparesis [20] has gradually become a hot topic.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] In addition, a comparison of the efficacy of various operation methods of POEM has gradually emerged, such as anterior versus posterior direction anterior versus posterior myotomy [25] and short versus standard esophageal myotomy. [26] At the same time, studies on the efficacy of POEM in the treatment of special populations such as the pediatric, [27] the geriatric, [28] the failed Heller myotomy patients, [29] and other esophageal motility disorders patients [30] are also gradually emerging. Recently, the efficacy of the derivative technology of POEM, such as D-POEM for esophageal diverticulum, [31] Z-POEM for Zenker diverticulum, [19] and G-POEM for refractory gastroparesis [20] has gradually become a hot topic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies showed that the length of circular myotomy is related to the occurrence of GERD complications. Short myotomy is safer and more effective than standard myotomy, which can reduce GERD complications [ 30 ]. It is still need for further study to decrease complications and enhance curative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding esophageal myotomy, a shorter myotomy (3–5 cm) on the esophageal side is comparable to a standard myotomy (7–10 cm) in terms of efficacy and safety. Two recent systematic reviews and meta‐analyses have demonstrated shorter operation time and reduction in the risk of postoperative GERD in a short myotomy group 16,17 . Shorter myotomy is suitable in type I and II patients, especially in type II patients.…”
Section: Poemmentioning
confidence: 99%
“…Two recent systematic reviews and meta-analyses have demonstrated shorter operation time and reduction in the risk of postoperative GERD in a short myotomy group. 16,17 Shorter myotomy is suitable in type I and II patients, especially in type II patients. However, we must remember that a longer myotomy is required in type III achalasia or other spastic disorders.…”
Section: Length Of Myotomymentioning
confidence: 99%